Time evolution of clusters of mobile particles in a model glass former - Appignanesi, Gustavo Adrian (2003)
In this work we investigate by means of molecular dynamics simulations the detailed time evolution of string-like cooperative motions in a binary Lennard–Jones system at temperatures close to its mode-coupling temperature, Tc. The strings will be fully geometrically and dynam- ically characterised, making evident the correlated and concerted nature of the motions of the particles comprised. We shall show that at low temperature each string occurs in a sharp time window within the time interval [0; t∗], where t∗ is a characteristic time related to the lifetime of the global clusters of mobile particles. Moreover, the di5erent strings that comprise a given global cluster will be shown to take place independently and asynchronically, thus providing further support to the heterogeneous scenario of relaxation, but in which di5erent independent string-like sub-regions relax at di5erent timescales. Finally, we shall also demonstrate that as temperature is increased the strings evolve during an increasing fraction of the time interval [0; t∗] and that for T ∼ 0:55 the lifetimes of the strings and of the global clusters become akin to each other.